Requisitos metrológicos legais para medição fiscal aplicados a unidades flutuantes de produção, armazenamento e transferência de petróleo - Lima Filho, Hélio Damásio de (Universidade Federal Rural do Semi-Árido, 2019)
The production of oil and natural gas in Brazil is of great importance, since it is by law a national commodity. The volume produced of this good directly influences the revenue of the union, states and municipalities, thanks to a series of national laws that promote the division of the resources derived from its exploitation. The most common sharing method is the collection of royalties, which are paid in an amount directly proportional to the flow produced by the field producer. Given the large volumes of current production, especially offshore on FPSO-type exploration platforms, strict metrological control is required. The Brazilian Petroleum and Natural Gas Regulatory Agency (ANP) is responsible for ensuring the correct measurement of this product, the measurement performed for this purpose is called tax measurement. To standardize and regulate volumetric oil measurements, the ANP has published a document governing the metrological requirements of metering systems. This document is called the Technical Regulation for Oil and Natural Gas Measurement (RTM). The selection of equipment that will make up the measurement system, how it should be designed and inserted into the process plant and the support mechanisms advocated by the RTM must meet legal metrological requirements and a number of national and international standards. A detailed study of regulatory and legal metrological documents governing tax measurement in Brazil will be undertaken in order to group the design and equipment selection requirements of an oil volume measurement system. The objective of this work is from these requirements to define national and international standards that can be applied to meet them. Knowledge about these standards and how to select system meters and accessories is of great importance. The system when finalized is designed to meet a number of pre-established conditions and is not fit for use, at least without a thorough analysis, at other fiscal measurement points.
Monografia
Keywords: Petróleo; Medição Fiscal; Requisitos Metrológicos; FPSO; Oil; Assessment measurement; Metrological requirements; ENGENHARIAS::ENGENHARIA DE PETROLEO